Effects of Orally Administered Lactoferrin and Lactoperoxidase-Containing Tablets on Clinical and Bacteriological Profiles in Chronic Periodontitis Patients - Eiju Shimizu; Tetsuo Kobayashi; Hiroyuki Wakabayashi; Koji Yamauchi; Keiji Iwatsuki; Hiromasa Yoshie (Hindawi Limited, 2011)
This study was undertaken to evaluate the effect of oral administration of lactoferrin (LF) and lactoperoxidase-(LPO-)containing tablet on periodontal condition. Seventy-two individuals with chronic periodontitis were randomly assigned to take either bovine LF and LPO-containing tablets (test group, n=37) or control tablets (control group, n=35) every day for 12 weeks. Periodontal parameters and levels of subgingival plaque bacteria, human and bovine LF, and endotoxin in gingival crevicular fluid (GCF) were evaluated at baseline, 1 week, 4 weeks, and 12 weeks. Significant differences were observed in GCF levels of bovine LF between the test and control groups throughout the study (P<.05). However, clinical and bacteriological parameter values proved comparable between the two groups at 1 week to 12 weeks. Therefore, the effect of oral administration of LF and LPO-containing tablets might be weak on periodontal and bacteriological profile in this study.